2017
DOI: 10.1111/cdoe.12291
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing patterns of analgesics and other medicines by dental practitioners in Australia from 2001 to 2012

Abstract: Dental prescribing of analgesics, anti-inflammatories and benzodiazepines in the concessional population has increased significantly over the past decade. These data can form the baseline to further examine appropriate medicine use in the management of dental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 19 publications
4
28
0
7
Order By: Relevance
“…There was an increase in the overall dispensed use of opioids (30%) more than previous findings (12%) . While it is not known if these were prescribed in conjunction with other analgesics or anti‐inflammatory drugs, the 30% increase is questionable and concerning, especially because opioids are not a first‐line treatment for dental pain.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…There was an increase in the overall dispensed use of opioids (30%) more than previous findings (12%) . While it is not known if these were prescribed in conjunction with other analgesics or anti‐inflammatory drugs, the 30% increase is questionable and concerning, especially because opioids are not a first‐line treatment for dental pain.…”
Section: Discussionmentioning
confidence: 76%
“…Currently, there is limited literature assessing dental prescribing patterns of medicines other than antibiotics. A recently published article assessed prescribing under the Pharmaceutical Benefits Scheme (PBS) of non‐antimicrobial medicines by dental practitioners for concessional beneficiaries from 2001 to 2012 in Australia and showed that the dental prescribing of analgesics, benzodiazepines and anti‐inflammatories had increased significantly over that time period . However, this analysis was undertaken for only those patients who were recipients of concessional benefits, and was unable to assess prescribing for the whole population under the PBS as that information was not available at the time…”
Section: Introductionmentioning
confidence: 99%
“…Recent longitudinal studies in Australia show that dental dispensed opioids have been increasing in recent years, including Panadeine Forte, ® tramadol and oxycodone and that it is established that drug seeking and drug dependent patients are common in general dental practice. Therefore dentists should be aware of the increasing issues relating to prescribing drugs of dependence such as opioids and benzodiazepines and the importance of establishing a true therapeutic need .…”
Section: Misuse Of Pharmaceutical Drugsmentioning
confidence: 99%
“…There is limited literature on dental prescribing of other medicines, but two retrospective studies in Australia indicated some divergence from guidelines for analgesic and anxiolytic prescribing, showing increasing dental use of opioids and benzodiazepines …”
Section: Introductionmentioning
confidence: 99%
“…12 There is limited literature on dental prescribing of other medicines, but two retrospective studies in Australia indicated some divergence from guidelines for analgesic and anxiolytic prescribing, showing increasing dental use of opioids and benzodiazepines. 13,14 It is well established that the use, particularly unnecessary use, of antibiotics is a major contributor to the development of antibiotic resistance. Appropriate prescribing, according to evidence-based indications, is therefore a professional responsibility of all clinicians, as collective use affects not only the individual but also the whole community and entire populations.…”
Section: Introductionmentioning
confidence: 99%